2014
DOI: 10.1016/j.scitotenv.2013.12.089
|View full text |Cite
|
Sign up to set email alerts
|

Foliar or root exposures to smelter particles: Consequences for lead compartmentalization and speciation in plant leaves

Abstract: In urban areas with high fallout of airborne particles, metal uptake by plants mainly occurs by foliar pathways and can strongly impact crop quality. However, there is a lack of knowledge on metal localization and speciation in plants after pollution exposure, especially in the case of foliar uptake. In this study, two contrasting crops, lettuce (Lactuca sativa L.) and rye-grass (Lolium perenne L.), were exposed to Pb-rich particles emitted by a Pb-recycling factory via either atmospheric or soil application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 69 publications
(77 reference statements)
0
35
1
Order By: Relevance
“…Recently, Schreck et al (2014) investigated the consequences on Pb compartmentalization and speciation in plant leaves of the method of exposure (foliar or root). The pollution context was the same as for the present study (i.e., atmospheric smelter particles).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schreck et al (2014) investigated the consequences on Pb compartmentalization and speciation in plant leaves of the method of exposure (foliar or root). The pollution context was the same as for the present study (i.e., atmospheric smelter particles).…”
Section: Discussionmentioning
confidence: 99%
“…Health risks associated with atmospheric Cd pollution arise mainly from inhalation of particles and consumption of polluted vegetables (Morman and Plumlee 2013). Although root-metal uptake is considered the main uptake pathway for plants, foliar uptake has also been identified as a potentially significant route of Cd exposure (Shahid et al 2013b;Schreck et al 2014;Xiong et al 2014a, b;Uzu et al 2010). Recently, Schreck et al (2013) suggested that root and shoot metal transfer pathways are independent, with an additive effect in terms of toxicity.…”
Section: Foliar Uptake Of CDmentioning
confidence: 99%
“…Aerial deposition onto leaves and fruits could explain such results [21,22]. Moreover, with the increasing quantities of ultrafine atmospheric particles in urban and peri-urban areas, foliar plant exposure could sometimes be the main route of plant pollution in aerial organs [23,120].…”
Section: Lack Of Data About Sb Localization In Plant Organsmentioning
confidence: 99%
“…Such variations could come from differences in leaf morphology, and/or changes in Sb speciation throughout the plant [23].…”
Section: Human Bioaccessibility Of Sbmentioning
confidence: 99%